Akt protects the heart against ischaemia-reperfusion injury by modulating mitochondrial morphology - Ong, Sang-Bing; Hall, Andrew R.; Dongworth, Rachel K.; Kalkhoran, Siavash; Pyakurel, Aswin; Scorrano, Luca; Hausenloy, Derek J. (Thrombosis and Haemostasis, 2015)
The mechanism through which the protein kinase Akt (also called PKB), protects the heart against acute ischaemia-reperfusion injury (IRI) is not clear. Here, we investigate whether Akt mediates its cardioprotective effect by modulating mitochondrial morphology. Transfection of HL-1 cardiac cells with constitutively active Akt (caAkt) changed mitochondrial morphology as evidenced by an increase in the proportion of cells displaying predominantly elongated mitochondria (73 ± 5.0 % caAkt vs 49 ± 5.8 % control: N=80 cells/group; p< 0.05). This effect was associated with delayed time taken to induce mitochondrial permeability transition pore (MPTP) opening (by 2.4 ± 0.5 fold; N=80 cells/group: p< 0.05); and reduced cell death following simulated IRI (32.8 ± 1.2 % caAkt vs 63.8 ± 5.6 % control: N=320 cells/group: p< 0.05). Similar effects on mitochondrial morphology, MPTP opening, and cell survival post-IRI, were demonstrated with pharmacological activation of Akt using the known cardioprotective cytokine, erythropoietin (EPO). The effect of Akt on inducing mitochondrial elongation was found to be dependent on the mitochondrial fusion protein, Mitofusin-1 (Mfn1), as ablation of Mfn1 in mouse embryonic fibroblasts (MEFs) abrogated Akt-mediated mitochondrial elongation. Finally, in vivo pre-treatment with EPO reduced myocardial infarct size (as a % of the area at risk) in adult mice subjected to IRI (26.2 ± 2.6 % with EPO vs 46.1 ± 6.5 % in control; N=7/group: p< 0.05), and reduced the proportion of cells displaying myofibrillar disarray and mitochondrial fragmentation observed by electron microscopy in adult murine hearts subjected to ischaemia from 5.8 ± 1.0 % to 2.2 ± 1.0 % (N=5 hearts/group; p< 0.05). In conclusion, we found that either genetic or pharmacological activation of Akt protected the heart against acute ischaemia-reperfusion injury by modulating mitochondrial morphology.
Keywords: Ischaemia; reperfusion; myocardial infarction; mitochondrial morphology; Akt